Optical Coherence Tomography Angiography Features in Post-COVID-19 Pneumonia Patients: A Pilot Study - Cennamo, Gilda; Reibaldi, Michele; Montorio, Daniela; D'Andrea, Luca; Fallico, Matteo; Triassi, Maria (American journal of ophthalmology, 2021)
This study investigated changes in retinal vessel density in macular and papillary regions in post-SARS-CoV-2 pneumonia patients by means of optical coherence tomography angiography (OCTA). Prospective, observational, cohort study. Forty eyes of 40 patients (mean age: 49.7 ± 12.6 years old) post-SARS-CoV-2 infection and 40 healthy subjects were enrolled in this study. COVID-19 patients had to be fully recovered from COVID-19 pneumonia and were evaluated 6 months after COVID-19 infection. The primary outcome resulted from OCTA studies of the following vascular structures: vessel density (VD) in the retinal superficial capillary plexus (SCP), deep capillary plexus (DCP), and radial peripapillary capillaries (RPC) compared to those of controls. Structural spectral domain (SD)-OCT parameters were also evaluated: ganglion cell complex (GCC) and retinal nerve fiber layer (RNFL). The patients showed a significant reduction in VD of the SCP in whole images and in the DCP in all sectors compared to those in healthy subjects (P <.05). COVID-19 patients featured a reduced VD of the RPC compared to that in controls (P <.001). No differences were found in the GCC, whereas the RNFL was reduced in the COVID-19 group compared to that in controls (P = .012). Significant correlations were found between the RNFL and VD of the SCP, DCP, RPC, and FAZ area in the COVID-19 group (P <.05). OCTA showed retinal vascular changes in subjects fully recovered from COVID-19 pneumonia. These findings could be a consequence of a thrombotic microangiopathy that affected retinal structures as well as other systemic organs. OCTA could represent a valid, noninvasive biomarker of early vascular dysfunction after SARS-CoV-2 infection.